Information visualization with vocabulary tracking for word recognition in Qur’anic verses / Raja Jamilah Raja Yusof - Raja Jamilah, Raja Yusof (2011)
Muslims read or recite the Qur‘an which is a source of guidance in all aspects of life. However, their recitation is sometimes without comprehension especially to those who do not understand Arabic language. To help reduce this comprehension problem, visualization is proposed based on the theory that the learning process involves the perception and the processing stages. In particular, the visualization helps to support the perception stage and is used as a strategy to solve the word recognition with meaning retrieval problem. The occurrences of the Arabic words are visualized since the Qur’anic verses contain many repeated words. This is achieved through Parallel Coordinate and word segmentation visualization technique. The next stage is to process the information and this is supported through a vocabulary tracking system. The system is able to track a user‘s personal vocabulary with the presentation of the percentage and position in context of the Qur’an. In direct consequence the users know their ability of recognizing the Arabic words in relation to the whole Qur’an to achieve reading comprehension. The hypothesis is that visualization with vocabulary tracking mechanism supports Arabic word recognition in the Qur‘anic verses. The research methodology of this thesis starts with a preliminary study of identifying problems of Qur’an reciters and in solving the problem a study was carried out on how visual elements can help in reading comprehension. Then, an interface system called Parallel Coordinate of the Qur’an (PaCQ) was developed with appropriate functions and finally tested for its effectiveness. Particularly, PaCQ was tested for any improvement in the word recognition percentage scores and the time taken to complete word recognition exercise. An experimental study was set up starting with a pre-test of Arabic Word Recognition Test (AWRT) to all the targeted participants. Then stratified sampling was used to divide the participants into the control and the experimental group for the AWRT post-test. It was found that the AWRT score percentage rank for participants after using PaCQ interface was significantly higher compared to before using PaCQ. The average AWRT percentage scores of set 4, 5 and 6 (the post-test) for the PaCQ group, show significant difference in the rank score compared to the control group. The average rank time to complete the post-test for the PaCQ group is significantly faster compared to the control group. The average time to complete AWRT for age group >= 35 had been significantly improved in the experimental group compared to the control group. It can be concluded that visualization and vocabulary tracking mechanism through the PaCQ interface improve word recognition performance both in the score and the time taken to complete the test.